2015
DOI: 10.1002/ajim.22527
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanates and work‐related asthma: Findings from California, Massachusetts, Michigan, and New Jersey, 1993–2008

Abstract: Background Isocyanates remain a leading cause of work-related asthma (WRA). Methods Two independent data systems were analyzed for the period 1993–2008: (1) State-based WRA case surveillance data on persons with isocyanate-induced WRA from four states, and (2) Occupational Safety and Health Administration (OSHA) Integrated Management Information System (IMIS) isocyanate air sampling results. Results We identified 368 cases of isocyanate-induced WRA from 32 industries and 678 OSHA isocyanate air samples with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…13 Health effects of isocyanate have been well documented in the literature, including but not limited to increased risk of asthma and contact dermatitis. [14][15][16][17] In an in-vitro cytotoxicity study, oral epithelial cells exposed to Invisalign aligners eluate showed increased cell death, compromised membrane integrity, and reduced cell-to-cell contact and mobility, which may be the mechanism for isocyanate allergy. 8 Forty-five MDRs reported a serious or lifethreatening event (per treating doctor).…”
Section: Discussionmentioning
confidence: 99%
“…13 Health effects of isocyanate have been well documented in the literature, including but not limited to increased risk of asthma and contact dermatitis. [14][15][16][17] In an in-vitro cytotoxicity study, oral epithelial cells exposed to Invisalign aligners eluate showed increased cell death, compromised membrane integrity, and reduced cell-to-cell contact and mobility, which may be the mechanism for isocyanate allergy. 8 Forty-five MDRs reported a serious or lifethreatening event (per treating doctor).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of such patients triggers a follow-up investigation, which includes evaluating worksite factors potentially responsible for asthma and screening other workers for asthma at the implicated worksite. Despite multiple limitations, these systems offer a unique opportunity to identify work-related asthma cases and related exposures [27,29]. Surveillance in the state of Michigan during 1988-2015 yielded 3417 work-related asthma cases.…”
Section: Work-related Asthma Death Case Reportsmentioning
confidence: 99%
“…We show that nano-molar concentrations of toluene diisocyanate (TDI) [9] , a notorious lung toxicant and respiratory sensitizer [10] , induce a sudden release of ATX from lung epithelial cells and we couple ATX to TDI toxicity [9] .…”
Section: Research Highlightmentioning
confidence: 99%
“…So the margin of safety is slim or absent for at least the ceiling value. Of further interest is that it has been claimed that current OELs in USA do not sufficiently protect workers as several cases of diisocyanate asthma were reported in recent years [10] . US OELs are higher than the Swedish OELs [10] so our data support this conclusion.…”
Section: Diisocyanates and Occupational Exposure Limits (Oels)mentioning
confidence: 99%
See 1 more Smart Citation